Komunikasi Persuasif Pada Film “Bolehkah Sekali Saja Kumenangis” Dalam Upaya Mengkampanyekan Isu Kesehatan Mental - Savira Nabila Azzahra; Asriyani Sagiyanto; Fajar Diah Astuti (Journal of Innovative and Creativity, 2025)
One of the social issues that has attracted public attention in recent years is mental health, because mental health can affect anyone from teenagers to adults. Negative stigma towards people with mental disorders remains a major obstacle to treatment and recovery. Mental health tends to be viewed as taboo, so many victims are reluctant or refuse to seek help. This study aims to determine how persuasive communication in the film “Bolehkah Sekali Saja Kumenangis” campaigns for mental health issues. The method used in this study is descriptive qualitative, and the theory used is the Elaboration Likelihood Model (ELM). The results of this study show that there are 14 central pathways and 6 peripheral pathways. The conclusion of the study is that there is persuasive communication displayed in the film “Bolehkah Sekali Saja Kumenangis” in campaigning for mental health issues by providing solutions for handling and changing behavior or attitudes, through the ELM theory with two pathways used, namely the central pathway through the film's dialogue script and the peripheral pathway through the emotional side, behavior, and body gestures depicted by the film's characters.